1990
DOI: 10.1002/jemt.1060150410
|View full text |Cite
|
Sign up to set email alerts
|

A replica technique for extracting precipitates from zirconium alloys for transmission electron microscopy analysis

Abstract: A reliable two-stage carbon replica technique has been developed to extract precipitates from zirconium alloys. Using this technique, all precipitating phases can be extracted from Zircaloy-2, Zr-Cr-Fe, and Zr-Nb-Fe alloys. Precipitate identification using EDS X-ray analysis and convergent beam electron diffraction was greatly facilitated in comparison to thin foils. In addition, the sensitivity for the detection of trace elements in particles was increased using extraction replicas. The chemical compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Two ternary intermetallic phases can be found in ZrNb, Fe, (Sn) alloys: a Laves phase with a hexagonal structure Zr(Nb, Fe) 2 (average chemical composition: Zr 35 Nb 35 Fe 30 ) and a fcc phase (Zr, Nb) 4 Fe 2 (average chemical composition: Zr 60 Nb 10 Fe 30 ) [15][16][17][18][19][20]. Moreover, cubic centered b Nb phases can be found.…”
Section: Second Phase Particlesmentioning
confidence: 99%
“…Two ternary intermetallic phases can be found in ZrNb, Fe, (Sn) alloys: a Laves phase with a hexagonal structure Zr(Nb, Fe) 2 (average chemical composition: Zr 35 Nb 35 Fe 30 ) and a fcc phase (Zr, Nb) 4 Fe 2 (average chemical composition: Zr 60 Nb 10 Fe 30 ) [15][16][17][18][19][20]. Moreover, cubic centered b Nb phases can be found.…”
Section: Second Phase Particlesmentioning
confidence: 99%
“…Interestingly, the authors observed no β-Nb phases within α-Zr when the alloy Nb content is 0.29 wt.% and did observe β-Nb when the Nb content was 0.49 wt.%. This leads to the conclusion that Nb TSS in α-Zr is in the range 0.29-0.49 wt.% at temperatures below the Zr-Nb monotectoid temperature (<600 °C), a value much greater than that suggested by Canay et al Figure 1 Ternary Zr-Nb-Fe diagram generated from data after [3,[20][21][22][23][24][25][26][27]29,[41][42][43][44]46,[62][63][64]. All compositions are given in at.%.…”
Section: Nb Terminal Solid Solubility In α-Zrmentioning
confidence: 99%
“…Under β-Zr decomposition, the possibility of Fe dispersing into α-Zr and/or present as binary Zr-Fe intermetallics has been suggested by some [35], and ternary ZrNbFe intermetallics have been demonstrated by others [13,19]. The existence of ternary ZrNbFe intermetallics has been shown in quaternary Zr-Nb-Sn-Fe alloys such as ZIRLO TM [34,40], NSF-2 [41] and E635 [20,24,27,[42][43][44], and has also been shown in Zr-1.25Nb (wt.%) [29] and in Zr-2.5Nb (wt.%), either standard pressure tubing containing Fe as an impurity, typically < 0.15 wt.% [45], or with added 0.1 and 0.5Fe (wt.%) [46]. An analysis of these ternary phases is to follow in section 5.…”
Section: The β-Nb Phase and "Where The Iron Goes"mentioning
confidence: 99%
“…The conditions used were as specified by Cocks et al (19771, with an aluminum cathode and the current density maintained at -10mA/cm2. Carbon replicas were produced using the two-stage extraction technique, as described elsewhere (Bradley, 1965;Ng-Yelim et al, 1990). Briefly, a Bioden (Oken Shoji Co., Tokyo) acetylcellulose replication film, softened using acetone, was laid on the etched specimen surface.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The technique of extraction of second-phase particles for analysis using transmission electron microscopy (TEM), once the principal domain of steels research (Bradley, 1965), has undergone something of a renaissance in recent years (Hasan et al, 1982;Ng-Yelim et al, 1990). During a recent project on Mg alloys, part of which is reported elsewhere (Mitrovic-Scepanovic et al, 1994), we found it necessary to examine the microstructures of several alloys using TEM.…”
Section: Introductionmentioning
confidence: 99%